A Technique for Section Thickness Evaluation for Microphotometry and Image Analysis of Sectioned Nuclei - R. L. Cabrini; A. Folco; S. Orrea; M. T. Savino; A. M. Schwint; M. E. Itoiz (Analytical Cellular Pathology)
The exact knowledge of the section thickness is a requisite for making the necessary corrections on DNA measurements in tissue sections. Several methods have been proposed to evaluate section thickness, each of them with advantages and disadvantages depending on the type of specimen and equipment available. We herein report another method based on preparation of standard material whose optical density varies as a function of its thickness and is sectioned and measured alongside the tissue specimen. The standards consist of celloidin cylinders stained with the PAS reaction and embedded in paraffin. For prior characterization of the cylinders, sections of different thickness were obtained and mounted. The optical density of each section was measured by direct microphotometry or image analysis. The actual thickness of each section was evaluated following re-embedding of piled groups of sections in a paraffin block and transversal sectioning. The thickness was then measured with a micrometric eye-piece. Optical density and actual thickness of each section were plotted on a normogram curve. Once a given tissue is sectioned alongside with the reference cylinder, the actual thickness is determined by its optical density on the normogram curve.